Response to Comment on ˜Existence domains of slow and fast ion-acoustic solitons in two-ion space plasmas" [Phys. Plasmas 23, 064701 (2016)] - Singh, S. V.; Lakhina, G. S. (My University, 2016)
In a note, Olivier et al.1 have commented on the paper entitled, “Existence domains of slow and fast ion-acoustic solitons in two-ion space plasmas,” Phys. Plasmas 22, 032313 (2015), by Maharaj et al.2 claiming that expressions for the Sagdeev potential given here and in two other papers by Maharaj et al.3,4 are incorrect.
Keywords: Ion-acoustic solitons; Ion-acoustic solitons; Sagdeev pseudo-potential formalism